THE EFFECTS OF TEACHING TECHNIQUE AND VOCABULARY MASTERY TOWARDS STUDENT’S WRITING SKILL (Experiment at State Vocational High Schools in Karawang) - Asep Darojatul Romli (Universitas Buana Perjuangan Karawang, 2016)
ABSTRACT The aim of this research is to know if there are effects of teaching technique and vocabulary mastery towards student’s writing skill at State Vocational High Schools in Karawang West Java. The population of this research is all the state vocational high school students in Karawang. Meanwhile, the sample of this research is 60 students from two schools taken randomly. This research is experimental research with two factors; teaching technique using guessing song and conventional technique and vocabulary mastery. The data about vocabulary mastery and writing skill are taken through tests. It has tested the validity and reliability test. The data analysis, the researcher used SPSS (Statistical Product and Service Solution) Program version 17,00. The result of data 1) There is a significant effect of teaching technique towards student’s writing skill. It is proved by Fo = 46.796 and sig = 0.000